Choroidal and retinal exudative changes following extensive endolaser pan retinal photocoagulation - Priyanka Gandhi; Vishma Prabhu; Prathiba Hande; Rupal Kathare; Ayushi Choudhary; Jay Chhablani; Ramesh Venkatesh (BMC Ophthalmology, 2024)
Abstract Background In this report, we describe a case of proliferative diabetic retinopathy that developed into exudative changes confusing with central serous chorioretinopathy (CSCR) following extensive endolaser pan retinal photocoagulation. Case description A 49-year-old male patient with diabetic retinopathy in both eyes presented with vitreous hemorrhage and 6/60 visual acuity in his left eye. Optical coherence tomography (OCT) scans at presentation revealed serous PEDs in both eyes. On day 10 after vitreoretinal surgery and complete peripheral endolaser PRP for the left eye, there was serous retinal detachment (SRD) and an increase in PED heights, mimicking CSCR. No additional treatment was considered. At the three-week post-operative visit, OCT scans revealed that the SRD had resolved and the PED heights had decreased without rupture. At the final follow-up visit, 12 weeks after surgery, the SRD had not recurred, and the PEDs had stabilized. Despite no additional ocular therapy for the right eye, the serous PED height had decreased. The choroidal thickness (CT) at the fovea at various points during the follow-up visits revealed a reduction in both eyes. Conclusion This case demonstrated the course of SRD, PED, and CT following extensive PRP. These changes may be associated with intraocular VEGF changes. In the presence of SRD and serous PED, the PED morphology may help differentiate the condition from CSCR. Although caution should be exercised when performing PRP during surgery or as an outpatient procedure, the SRD usually resolves without problem.